CMet agonistic antibody attenuates apoptosis in ischaemia‐reperfusion–induced kidney injury. Issue 10 (2nd April 2020) - An, Jung Nam; Li, Lilin; Lee, Junghun; Yu, Seung‐Shin; Lee, Jeonghwan; Kim, Yong Chul; Kim, Dong Ki; Oh, Yun Kyu; Lim, Chun Soo; Kim, Yon Su; Kim, Sunyoung; Yang, Seung Hee; et al.
Abstract: Acute kidney injury (AKI) is a very common complication with high morbidity and mortality rates and no fundamental treatment. In this study, we investigated whether the hepatocyte growth factor (HGF)/cMet pathway is associated with the development of AKI and how the administration of a cMet agonistic antibody (Ab) affects an AKI model. In the analysis using human blood samples, cMet and HGF levels were found to be significantly increased in the AKI group, regardless of underlying renal function. The administration of a cMet agonistic Ab improved the functional and histological changes after bilateral ischaemia‐reperfusion injury. TUNEL‐positive cells and Bax/Bcl‐2 ratio were also reduced by cMet agonistic Ab treatment. In addition, cMet agonistic Ab treatment significantly increased the levels of PI3K, Akt and mTOR. Furthermore, after 24 hours of hypoxia induction in human proximal tubular epithelial cells, treatment with the cMet agonistic Ab also showed dose‐dependent antiapoptotic effects similar to those of the recombinant HGF treatment. Even when the HGF axis was blocked with a HGF‐blocking Ab, the cMet agonistic Ab showed an independent dose‐dependent antiapoptotic effect. In conclusion, cMet expression is associated with the occurrence of AKI. cMet agonistic Ab treatment attenuates the severity of AKI through the PI3K/Akt/mTOR pathway and improves apoptosis. cMet agonistic Ab may have important significance for the treatment of AKI.